Pengembangan Ekosistem Usaha Wisata Halal Bebas Pungli Berbasis Manajemen Bisnis Syariah di Kawasan Sentul Kabupaten Bogor - Ferdinand, Novingky; Hasan, Sawqi Saad El; Herawati, Ermi; Suherman, Cecep; Darmawan, Dedy (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2025)
Halal tourism development in Sentul, Bogor, is hindered by illegal levies (pungli) and the lack of halal certification, which damage tourist trust. This community service aims to establish an extortion-free business ecosystem based on Sharia Business Management. Using the Participatory Action Research (PAR) method with four partners, activities included social mapping, participatory planning, and assistance for NIB and halal certification via SIHALAL. Success was evaluated using the Policy Acceptance Model (Vlassenroot et al., 2008). Results show significant transformation: four partners successfully completed the halal certification submission process, and an "Extortion-Free Tourism Zone" was established with transparent tariff standardization. Vlassenroot analysis reveals that partner acceptance of the new system was driven by a shift in social norms towards blessing-oriented business (General Indication) and the perception of tangible economic benefits from business legality (System Specific Indication). This intervention proved effective in transforming informal economic actors into ethical, legal, and sustainable tourism business entities.